Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper reviews Uruguay's experience with inclusive growth over the last two decades, and identifies challenges and policy options to promote greater equality going forward. Uruguay has a long history of high living standards comparable to many developed countries, and has made further progress in improving social conditions since 2005 on the back of strong economic growth and active social policies. Looking ahead, preserving macroeconomic stability is essential to sustain these gains. For the longer term, improving access to quality education will be the key to enhance social mobility.